Membangun Komunitas Online: Studi Etnografi Digital tentang Dinamika Kelompok di Platform Whatsapp - Rosyadi, Maruf (Komunika : Jurnal Ilmiah Komunikasi, 2024)
This study will analyze group dynamics in online communities and how interactions between community members occur. The existence of Whatsapp makes it easy for community members to share their ideas, information, and experiences. Using digital ethnography methods, data was collected using observation, interview, and content analysis techniques to study online groups and communities. In this study, it was found that educational discussion groups on the Whatsapp platform were very active and interactive in sharing information, expressing opinions, and providing support in terms of education. In addition, there was also a tendency for small subgroups to form with the same educational interests and goals. Goals, rules, and interactions between group members are the main factors that influence group dynamics on Whatsapp.